Student Perceptions of Peer Evaluation in an Online RN-to-BSN Course. Issue 6 (November 2018) - Kim-Godwin, Yeoun Soo; Turrise, Stephanie; Lawson, Sarah; Scott, Melissa
Abstract : The purpose of this study was to explore student perceptions of peer-evaluation experiences in an online RN-to-BSN nursing research course. A total of 140 students completed the online survey. A majority of students reported their peer-evaluation experience was helpful for learning (69%), and 81.8% of students indicated their writing skills improved. Findings of the study support the use of peer evaluation in online nursing courses. Abstract : Supplemental digital content is available in the text.